The Market-Oriented Development of China’s Carbon Emissions Trading: Based on the Comparative Analysis of China and EU - Runhong Lin; Tongjuan Cai (Energies)
We mainly focus on the degree of marketisation of China’s carbon emissions trading from two aspects. Firstly, based on the financial market theory, the different characteristics of the construction of the EU and China’s carbon emissions trading market are compared. Secondly, the VAR-MVGARCH-DCC model is used to empirically analyze the dynamic correlation between the carbon emissions trading market and the stock market. The results show that the marketisation degree of China’s carbon emissions trading still has much room for improvement compared with the EU, and the carbon emission market has a significant guiding effect on the stock market. Therefore, to improve the carbon emissions trading system, we should pay attention to the influence of financial factors on carbon emissions trading and the establishment of transmission channels from the carbon market to the stock market. It is recommended to learn from the experience of the European Union and to take key industries as a guide to create a modern carbon financial system with more Chinese characteristics.